Dummy humanoid robot simulating several trunk postures and abdominal shapes – Report of element technologies. (19th March 2017) - Ogata, Kunihiro; Umino, Tokio; Nakayama, Tsuyoshi; Ono, Eiichi; Tsuji, Toshiaki
Graphical Abstract: Abstract : Development of clothing in consideration of the shape and body function of a person with spinal cord injury is an important task. Then, a dummy robot with a deformation mechanism was developed in this study for evaluating the comfortable level of clothings. Specifically, a trunk joint mechanism and an abdominal mechanism that can realize various deformations of the abdominal area and various trunk poses were developed. The trunk joint mechanism was implemented in order to simulate the seated posture of persons with spinal cord injury. The abdominal deformation mechanism was implemented using linear actuators and rotating servomotors in order to simulate abdominal obesity of persons with spinal cord injury. Further, a tactile sensor system was developed for measuring the clothing pressure on the abdominal area and evaluating the comfort or discomfort of clothing.